The prognostic significance of the immunohistochemical expression of p53, bcl-2, c-erb B-2 and cathepsin-D in ovarian cancer patients receiving platinum with cyclophosphamide or paclitaxel chemotherapy - Protopapas, A.; Diakomanolis, E.; Bamias, A.; Milingos, S.; Markaki, S.; Papadimitriou, C.; Dimopoulos, A.-M.; Michalas, S. (European Journal of Gynaecological Oncology, 2004)
Purpose: To evaluate the prognostic significance of the immunohistochemical expression of p53, bcl-2, c-erbB-2 and cathepsin-D in epithelial ovarian cancer (EOC). Methods: We analyzed 100 patients with ovarian carcinoma, FIGO Stage IC-IV who underwent primary cytoreductive surgery and received adjuvant chemotherapy with cyclophosphamide and a platinum analogue (CP) (n = 46) or paclitaxel and a platinum analogue (TP) (n = 54). Immunohistochemical expression was studied on paraffin-embedded tissue from the primary tumor. Results: After a median follow-up of 55 months median progression-free survival (PFS) and overall survival (OS) were 16 and 41 months, respectively. Positive bcl-2 staining and absence of cathepsin-D expression were associated with an increased complete response rate in the CP group (p = 0.011 and p = 0.003) but not in the TP group. PFS and OS were not associated with the expression of any of the markers studied. FIGO stage (p = 0.006) and histology (p = 0.047) were the only independent prognostic factors for survival. Conclusion: Bcl2 and cathepsin D expression are associated with response to CP but not TP chemotherapy. P53, bcl-2, c-erb B-2 and cathepsin D expression was not correlated with PFS and OS in our study.
Keywords: Bcl-2; c-erb B-2; Cathepsins; Ovarian cancer; p53; Paclitaxel